The influence of narratives on the internationalization process of international new ventures - Rolo, Joana de Jesus Lourenço (2019)
This thesis has as objective filling in the existing gap in international literature about the role of narratives during the implementation of an internationalization strategy in an international new venture. To answer the research question, I did a qualitative research based on a Portuguese firm. The data was collected mainly through interviews, and the findings came from the analysis of managers’ narratives. This study argues that narratives are an inherent part of the organization and a valuable resource in the internationalization process since they can be used to enhance a collective understanding and action from the organizational members. This thesis concludes that the construction of inadequate narratives by the Chief Executive Officer (CEO) and managers leads to a slow and inefficient internationalization process.